Circ_0102543 suppresses hepatocellular carcinoma progression through the miR‐942‐5p/SGTB axis - Shiming Yang; Dianye Wang; Rui Zhang (Annals of Gastroenterological Surgery, 2023)
Abstract Introduction Hepatocellular carcinoma (HCC) is one of the most serious cancers. Circular RNA (circRNA) has been reported to regulate the progression of HCC. Herein, the role of circ_0102543 in HCC tumorigenesis was investigated. Materials The expression levels of circ_0102543, microRNA‐942‐5p (miR‐942‐5p), and small glutamine rich tetratricopeptide repeat co‐chaperone beta (SGTB) were detected by quantitative real‐time PCR (qRT‐PCR). 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium Bromide (MTT) assay, thymidine analog 5‐ethynyl‐2'‐deoxyuridine (EDU) assay, transwell assay, and flow cytometry were conducted to explore the function of circ_0102543 in HCC cells and the regulatory mechanism among circ_0102543, miR‐942‐5p and SGTB in HCC cells. Western blot examined the related protein levels. Results The expression of circ_0102543 and SGTB was decreased in HCC tissues, while the expression of miR‐942‐5p was increased. Circ_0102543 acted as a sponge for miR‐942‐5p, and SGTB was the target of miR‐942‐5p. Circ_0102543 up‐regulation hindered tumor growth in vivo. In vitro experiments showed that overexpression of circ_0102543 significantly repressed the malignant behaviors of HCC cells, while co‐transfection of miR‐942‐5p partially attenuated these effects mediated by circ_0102543. In addition, SGTB knockdown increased the proliferation, migration, and invasion of HCC cells inhibited by miR‐942‐5p inhibitor. Mechanically, circ_0102543 regulated SGTB expression in HCC cells by sponging miR‐942‐5p. Conclusion Overexpression of circ_0102543 suppressed proliferation, migration, and invasion of HCC cells by regulating the miR‐942‐5p/SGTB axis, suggesting that circ_0102543/miR‐942‐5p/SGTB axis may be a potential therapeutic target for HCC.